ALGORITMA FLOWER POLLINATION UNTUK KENDALI OPTIMAL PADA SISTEM MULTI-MESIN DENGAN GUPFC - , MOHAMMAD MUSOFA MULYA PAMBUDY, Dr. Ir. Sasongko Pramono Hadi, D.E.A. ([Yogyakarta] : Universitas Gadjah Mada, 2014)
Demand for electricity continues to grow, so that the existing system is required to be able to generate and distribute electrical energy required to the consumer. The distribution of power is done through the transmission line with a limited capacity, which can cause problems for the operation of power system stability. Build generation, transmission and distribution system in addition to costs that are not small, the long development time as well, so we need a way so that electrical energy can be transferred more without the need to build a new transmission system , by optimizing the existing system. FACTS device can be applied in the transmission line to improve power distribution and power system stability. One type of FACTS is GUPFC, which is able to improve the stability of the system, ie to dampen oscillations in the rotor angle, angular velocity changes, and electrical power. The study was conducted to determine the stability of the multi-machine power system without and with attached GUPFC. Stability control using the PSS and POD are optimized by meta-heuristic methods Flower Pollination. The results showed the addition GUPFC on multi-machine system able to decrease the value of the initial oscillations, overshoot, and settling time that happened, and the eigenvalue shifting increasingly to the left away from the imaginary axis.